2021
DOI: 10.1177/02666669211054210
|View full text |Cite
|
Sign up to set email alerts
|

Undervalued, understaffed, underdeveloped, and underutilized? The status of public libraries in the eleven municipalities of rural Iloilo Province, Philippines

Abstract: Libraries, as service-oriented organizations, are being guided on every aspect of their operation by local and international standards. In the Philippines, public libraries are expected to adhere to the stipulations of the Philippine Standards for Public Libraries. This study was conducted to assess the adherence of the 11 municipal libraries in Iloilo Province to the following areas of the Standards: library administration, collection management, services and utilization, physical facilities, financial resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, in many regions with limited economic infrastructures, there is a shortage of qualified librarians and information professionals (Salman et al. , 2017; Stilwell, 2018; Estrullo-Suaga et al. , 2021).…”
Section: The Reality Of Public Libraries In Resource-scarce and Infra...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many regions with limited economic infrastructures, there is a shortage of qualified librarians and information professionals (Salman et al. , 2017; Stilwell, 2018; Estrullo-Suaga et al. , 2021).…”
Section: The Reality Of Public Libraries In Resource-scarce and Infra...mentioning
confidence: 99%
“…Public libraries require competent and well-trained staff to deliver quality services. However, in many regions with limited economic infrastructures, there is a shortage of qualified librarians and information professionals (Salman et al, 2017;Stilwell, 2018;Estrullo-Suaga et al, 2021). Limited opportunities for professional development and training further exacerbate this issue, hindering the ability of libraries to keep pace with technological advancements and evolving user needs.…”
Section: The Reality Of Public Libraries In Resource-scarce and Infra...mentioning
confidence: 99%
“…The study results revealed that 5% of the study participants noted that the number of chairs and tables was insufficient, affecting the reduced number of patrons who visited the library. Thus, patrons do not exploit the library service quality if it is available (Estrullo-Suaga et al, 2023).…”
Section: Respondents' Opinions On What Services Constitute Qlismentioning
confidence: 99%